(3eMGSHI GdJcGdja (B:s (3eONd MOjK (B/s - (3YOS, fGFds; (3eMeO dNda, fVGds ((3YeGf(B: s (3OGQ GdjGRhQj GdYdjeI(B, s, 2012)
-(3GSGSjGJ eMGSHI GdJcGdja,JHhjH YfGUQ GdJcGdja,fXQjGJ GdJcGdja,GdQbGHI Ydi YfUQ JcdaI GdehGO,GdQbGHI Ydi JcdaI GdGLhQ,GdQbGHI Ydi YfUQ GdeUQhaGJ,fXGe JcGdja GdChGeQ GdJTZjdjI,fXGe JcGdja GdeQGMd GdGfJGLjI ,JcGdja GdefJLGJ GdeTJQcI hGdYQVjI(B.s
(3GdeQGLY U(B.465 ((3GbJfGAGJ (B2014 3(3f,(B2008)s
Keywords: (3GdQbGHIs; (3GdeMGSHIs; (3eMGSHI GdJcGdjas